A study of effects of different impact loads on the dynamic and elastoplastic behavior in reservoir rocks at the beginning of hydraulic fracturing - Abulimiti, Aibaibu; Wang, Linsheng; Zang, Chuanzhen; Chen, Bo; Xiang, Xinsheng; Jiang, Peijia; Lin, Jiaying (Frontiers in Earth Science, 2023)
Successful hydraulic fracturing is very important in the development of hydrocarbon-bearing formations. The loading introduced by hydraulic fracturing causes deformation and failure, which are related to the damage accumulation and hydraulic fracture initiation process. This study employs a numerical model that considers the dynamic and elastoplastic behaviors in rocks under the influence of impact loads. The acceleration and wave propagation behaviors are quantified using the model. A time integration algorithm is used to ensure numerical accuracy and stability. The effects of loading rate, loading location, and heterogeneity are quantified. Results show that the elastoplastic and dynamic can effectively capture the wavy mechanical responses in the domain. Strain rate, acceleration, and plasticity can all exhibit oscillatory distribution patterns. Increasing the loading rate can magnify acceleration, strain rate, and the maximum plastic strain, while it reduces the range experiencing these induced changes.Changing the loading types and introducing the heterogeneity consideration both largely alter the mechanical response in the domain, and the waveforms of the mechanical parameters are significantly changed. Failure can occur earlier in layers with more elastic mechanical properties. Exerting 50 MPa loading in 0.01 ms can effectively introduce deformation and failures in the reservoir rock. Doubling the loading rate can effectively improve the ability of creating rock failures, which facilitates the following fracture initiation and propagation processes. This study can be a reference for the understanding of nearwell and instantaneous rock mechanical behaviors at the beginning of fracturing.